Development of Picture Card Media for Science Learning at Elementary School - Aris Fadlan; Namiroh Lubis; Nurzakiah Simangunsong; Ahmad Tarmizi Hasibuan (Program Studi Pendidikan Guru Madrasah Ibtidaiyah INSURI Ponorogo, 2026)
This study aims to determine the development of card media (picture cards) in science learning for Grade III students in MIN 6 Medan city. This research is a Research and Development (R&D) research with the ADDIE development model, namely analysis, design, development, implementation, and evaluation. The subject of this study is a class III student at MIN 6 Medan city. The research instruments are in the form of questionnaires/questionnaires, test instruments, student response instruments, and teacher response instruments. The collected data were analyzed descriptively using percentage techniques. The results showed that: (1) picture card media for animal food chain material was successfully developed; (2) the validity test results showed a score of 73% from the material expert, categorized as valid, 85% from the media expert, categorized as very valid, and 100% from the practitioner/teacher, categorized as very valid; and (3) the practicality test results showed 99% in the initial trial, 95% in the field trial, and 91% based on the teacher’s response, all categorized as very practical. Therefore, the developed picture card media are feasible for use in science learning for Grade III elementary school students. This study was limited to the development, validity, and practicality of the media and did not directly measure improvement in students’ learning outcomes.